2016
DOI: 10.4168/aair.2015.8.1.41
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction Between Prenatal Exposure to Home Renovation and Reactive Oxygen Species Genes in Cord Blood IgE Response is Modified by Maternal Atopy

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.Purpose: Although home renovation exposure during childhood has been identified as a risk factor for the development of allergy, there is limited information on the association between prenatal exposure to home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Exposure to household renovation during the prenatal period was associated with significantly higher levels of cord blood IgE. Household renovation before pregnancy has also been shown to be associated with higher levels of IgE in neonates, a potential biomarker of infant allergic rhinitis 43 . Air pollutants such as indoor smoke, 44 phthalate esters, 45,46 and volatile organic compounds 47 have also been shown to be associated with higher concentrations of total blood IgE.…”
Section: Discussionmentioning
confidence: 98%
“…Exposure to household renovation during the prenatal period was associated with significantly higher levels of cord blood IgE. Household renovation before pregnancy has also been shown to be associated with higher levels of IgE in neonates, a potential biomarker of infant allergic rhinitis 43 . Air pollutants such as indoor smoke, 44 phthalate esters, 45,46 and volatile organic compounds 47 have also been shown to be associated with higher concentrations of total blood IgE.…”
Section: Discussionmentioning
confidence: 98%
“…One study in a predominantly black sample reported that three IL13 SNPs (rs1295686, rs1800925 and rs206974) could jointly influence CBIgE concentration [3]. One study in a birth cohort in Korea identified interactions between reactive oxygen species genes, prenatal exposure to home renovation and maternal atopy on CBIgE response [28]. Another study, in a Chinese population in Taiwan, found that IL13 rs20541, male sex and prenatal environmental tobacco smoke interacted on antenatal IgE production [5].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted to test the hypothesis that home renovation increases the risk of childhood eczema. Exposure to home renovation during the prenatal period has been found to be associated with significantly higher levels of cord blood IgE . Home renovation before pregnancy has also been investigated as potentially associated with incidence of atopic dermatitis in infants with higher levels of IgE .…”
Section: Discussionmentioning
confidence: 99%